2023
DOI: 10.1186/s12885-023-11449-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the expression of TET2 and DNA 5-hmC predict poor prognosis in Myelodysplastic Neoplasms

Ashikh A. Seethy,
Karthikeyan Pethusamy,
Tushar Kushwaha
et al.

Abstract: Background Myelodysplastic Neoplasms (MDS) are clonal stem cell disorders characterized by ineffective hematopoiesis and progression to acute myeloid leukemia, myelodysplasia-related (AML-MR). A major mechanism of pathogenesis of MDS is the aberration of the epigenetic landscape of the hematopoietic stem cells and/or progenitor cells, especially DNA cytosine methylation, and demethylation. Data on TET2, the predominant DNA demethylator of the hematopoietic system, is limited, particularly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…As another example, Seethy et al in 2023 demonstrated a reduction in TET2 expression among patients with high-or very-high-risk MDS per the Revised International Prognostic Scoring System (IPSS-R) and myelodysplasia-related AML (AML-MR in WHO5), as compared to patients with low-or intermediate-risk. The authors also noted that levels of 5-hydroxymethyl cytosine were concordantly lower [8]. The ICC 2022 recognizes MDS founding lesions and mutations in the following genes: ASXL1, BCOR, EZH2, RUNX1, SF3B1, SRSF2, STAG2, U2AF1 and ZRSR2 [9].…”
Section: Molecular Evolution Of Mds From Genotype To Phenotype and Pr...mentioning
confidence: 95%
“…As another example, Seethy et al in 2023 demonstrated a reduction in TET2 expression among patients with high-or very-high-risk MDS per the Revised International Prognostic Scoring System (IPSS-R) and myelodysplasia-related AML (AML-MR in WHO5), as compared to patients with low-or intermediate-risk. The authors also noted that levels of 5-hydroxymethyl cytosine were concordantly lower [8]. The ICC 2022 recognizes MDS founding lesions and mutations in the following genes: ASXL1, BCOR, EZH2, RUNX1, SF3B1, SRSF2, STAG2, U2AF1 and ZRSR2 [9].…”
Section: Molecular Evolution Of Mds From Genotype To Phenotype and Pr...mentioning
confidence: 95%